Curricular contribution of the subject Health and Philosophy to the educational process of Basic General Doctors. - Blanca Rosa Garcés Garcés; Irma Pasarón Pérez; Lázaro Delgado Moreira; Antonio Armas Vázquez (Medisur)
Background: The curriculum of Philosophy and Health discipline is an important tool in the formative process of General Comprehensive Doctors if the educative and instructive goals, as well as the content of each subject are linked to the educative work necessities and the future fields of Health Professionals. Objectives: To determine the curricular contribution of this discipline to the formative process of General Comprehensive Doctors regarding human values development, skills and preparation for their future working fields during courses 2000-2001, 2001-2002 and 2003-2004. Methods: An anonym survey was performed to students, in the conformation of the final report different methods were used: analysis, synthesis, historical-logical method. Results: Values such responsibility, discipline, justice, humanism, solidarity, honesty, anti-imperialism, equality and creativity were more popular among students and the least popular were simplicity and unconditional behavior. Conclusion: This experience allowed us to verify that this discipline has contributed to human values development of first year students and that they acknowledge their professor's work.